Perancangan Sistem Manajemen Mutu Departemen Produksi PT. X - Evander Lucius Azareel; Felecia Felecia (Jurnal Titra, 2022)
This research was conducted to design a Quality Management System in the Production Department PT. X. This company has increased their production capacity with a significantly increased demand. Thus there will be 7000 additional employees. Difference in production output happens with additional employees that needs to be fixed due to defect product triggering. Standaritation on every process needs to be done with a system that fits company needs. The standaritations trial could be done through a quality management system towards the production department. The document will be used to support the quality management in the future. The designing was done through observing and direct interview to operator and related admin. The observation’s result will be supporting data in the designing of the quality  management system in PT. X. The designed document is next to be evaluated and validated by the supervisor and head of production and cones. The validated document then will be stored as a written guidelines for the production process. The result is SOP, Work Instruction, Business Process, Quality Plan and Supporting Form. The documents will be given to related employees and become the documents that will be placed in several spots throughout the company as a retraining way to minimize the defect products.